Evaluation of the Relation between Asthma, Obesity and Leptin Level in Iraqi Asthmatic Patients and the Main Risk Factors that are Associated with Leptin Level - Hiba A. Hasan (College of Pharmacy University of Baghdad, 2017)
This study tries to clear the correlation and association between asthma, obesity and leptin levels. Also it will work to indicate the main risk factors which play role in the elevation of leptin level within asthmatic patients.  This is a case control study conducted on (38) asthmatic patients and (20) healthy control who were closely similar by age, gender and BMI. The main statistical tests used were student t test, linear regression test and correlation test. Significance was set at P < 0.05. Sampling method used for this study was convenience sampling method.  The main results of this study show a significant association and positive correlation between age (old age  â‰¥ 40 years old), female gender, BMI (overweight and obese) and steroid utilization with leptin elevation in Iraqi asthmatic patients since P values < 0.05. This study concludes that there is a correlation between obesity, age, sex and utilization of steroid with leptin level and they were the main risk factors which play role in the mechanism of elevation of leptin in Iraqi asthmatic patients. Key words: Leptin, Asthma, BMI.